Emotion Recognition: Photoplethysmography and Electrocardiography in Comparison - Sergio Rinella; Simona Massimino; Piero Giorgio Fallica; Alberto Giacobbe; Nicola Donato; Marinella Coco; Giovanni Neri; Rosalba Parenti; Vincenzo Perciavalle; Sabrina Conoci (Biosensors, 2022)
Automatically recognizing negative emotions, such as anger or stress, and also positive ones, such as euphoria, can contribute to improving well-being. In real-life, emotion recognition is a difficult task since many of the technologies used for this purpose in both laboratory and clinic environments, such as electroencephalography (EEG) and electrocardiography (ECG), cannot realistically be used. Photoplethysmography (PPG) is a non-invasive technology that can be easily integrated into wearable sensors. This paper focuses on the comparison between PPG and ECG concerning their efficacy in detecting the psychophysical and affective states of the subjects. It has been confirmed that the levels of accuracy in the recognition of affective variables obtained by PPG technology are comparable to those achievable with the more traditional ECG technology. Moreover, the affective psychological condition of the participants (anxiety and mood levels) may influence the psychophysiological responses recorded during the experimental tests.